Immune activation during cerebellar dysfunction following Plasmodium falciparum malaria. - de Silva, H; Hoang, P; Dalton, H; de Silva, N; Jewell, D; Peiris, J (1992)
Evidence for immune activation was investigated in 12 patients with a rare syndrome of self-limiting, delayed onset cerebellar dysfunction following an attack of falciparum malaria which occurred 18-26 d previously. Concentrations of tumour necrosis factor, interleukin 6 and interleukin 2 were all significantly higher in serum samples of patients during cerebellar ataxia than in recovery sera and in the sera of 8 patients who did not develop delayed cerebellar dysfunction following an attack of falciparum malaria. Cytokine concentrations in the cerebrospinal fluid were also significantly higher in ataxic patients than in controls. These findings suggest that immunological mechanisms may play a role in delayed cerebellar dysfunction following falciparum malaria.